Depression Management Physician Order: New initiatives at the Mental Hospital of Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Alsolami, Nora; Alqahtani, Nada; Rahbini, Abdulrahman (Journal of Pharmacy Practice and Community Medicine)
The general administration of pharmaceutical care stated evidence-based pharmacy guidelines at Ministry of Health hospitals and primary healthcare centers in 2015. That has included several programs related to anticoagulation, pain management, and antibiotics. The new initiative’s project from the most significant mental hospital in Riyadh region of starting psychiatric disease drug therapy management physician order. The hospital started with a standard disease like depression. The tax force team designed the updated guidelines and approved by an official body in the hospital. The form friendly used and very important in preventing drugrelated problems and education system for healthcare staff.
Keywords: Depression management; Physician Oder; Ministry of Health; Saudi Arabia